The Unequal Effects of Pollution on Labor Supply - Hoffmann, Bridget; Rud, Juan Pablo (Econometrica, 2024)
We use high‐frequency data on fine particulate matter air pollution (PM 2.5) at the locality level to study the effects of high pollution on daily labor supply decisions in the metropolitan area of Mexico City. We document a negative, non‐linear relationship between PM 2.5 and same‐day labor supply, with strong effects on days with extremely high pollution levels. On these days, the average worker experiences a reduction of around 7.5% of working hours. Workers partially compensate for lost hours by increasing their labor supply on days that follow high‐pollution days. We find that low‐income workers reduce their labor supply significantly less than high‐income workers. Unequal responses to high pollution along other dimensions (job quality, flexibility, gender) matter, but less than income. We provide suggestive evidence that reductions in labor supply due to high pollution are consistent with avoidance behavior.